Patrimonial Reflections: From Burning Buildings to Bodies of Heritage - Hafstein, Valdimar (Ethnologies, 2014)
The author of this paper argues that the rise of cultural heritage is perhaps the chief example of a newfound valuation of cultural practices and objects in terms of their expediency for economic and political purposes. This is culture as a resource: a novel configuration in which culture is now a central expedient in everything from creating jobs to reducing crime, from changing the face of cities through cultural tourism to managing differences and conflicts within the population. In this context, heritage provides a strong but flexible language for staking claims to culture and making claims based on culture. He suggests that the 2003 Convention for the Safeguarding of the Intangible Cultural Heritage signals a reformation of global heritage policy. Where earlier UNESCO efforts were content to document and archive expressions of folklore and traditional culture, its intangible heritage initiatives aim to assure the transmission and continuity of traditional practices in situ. This requires direct intervention in the communities involved. UNESCO enlists intangible heritage as an instrument for safeguarding community, a social and moral good perceived to be threatened by globalization. Intangible heritage has emerged as an instrument in the production of a strong (but not exclusive) sense of belonging for members of cultural communities within (and sometimes across) states. Population groups objectify their practices and expressions as “intangible heritage” and at the same time they subjectify themselves as “communities”. Government can then act on the social field through communities and by means of, among other things, heritage policies. The author also points out that many heritage practices take the body as their central objects – they turn the body into a site of performance. Indeed, intangible heritage is very much about the ways in which culture is embodied and the ways in which bodies are cultured.